PERAN MEDIA SOSIAL SEBAGAI SUMBER BELAJAR PAI: Analisis Inovasi dan Distorsi Nilai - Moh Said Aqil Hasan; Faisol Hakim (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
In the digital era, social media has become an important medium in conveying Islamic teachings and learning Islamic Religious Education (PAI). This research is a descriptive qualitative study with a document study and case study approach. This study analyzes the video content of